Resolved low-J12CO excitation at 190 parsec resolution across NGC 2903 and NGC 3627 - Brok, Jakob den; Leroy, A K; Usero, A; Schinnerer, Eva; Rosolowsky, Erik; Koch, E W; Querejeta, Miguel; Liu, D; Bigiel, Frank; Barnes, Ashley T.; Chevance, Mélanie; Colombo, Dario; et al. (Monthly notices of the Royal Astronomical Society, 2023)
The low-J rotational transitions of 12CO are commonly used to trace the distribution of molecular gas in galaxies. Their ratios are sensitive to excitation and physical conditions in the molecular gas. Spatially resolved studies of CO ratios are still sparse and affected by flux calibration uncertainties, especially since most do not have high angular resolution or do not have short-spacing information and hence miss any diffuse emission. We compare the low-J CO ratios across the disc of two massive, star-forming spiral galaxies NGC 2903 and NGC 3627 to investigate whether and how local environments drive excitation variations at GMC scales. We use Atacama Large Millimeter Array (ALMA) observations of the three lowest-J CO transitions at a common angular resolution of 4 arcsec (190 pc). We measure median line ratios of $R_{21}=0.67^{+0.13}_{-0.11}$, $R_{32}=0.33^{+0.09}_{-0.08}$, and $R_{31}=0.24^{+0.10}_{-0.09}$ across the full disc of NGC 3627. We see clear CO line ratio variation across the galaxy consistent with changes in temperature and density of the molecular gas. In particular, towards the centre, R21, R32, and R31 increase by 35 per cent, 50 per cent, and 66 per cent, respectively, compared to their average disc values. The overall line ratio trends suggest that CO(3-2) is more sensitive to changes in the excitation conditions than the two lower J transitions. Furthermore, we find a similar radial R32 trend in NGC 2903, albeit a larger disc-wide average of $\langle R_{32}\rangle =0.47^{+0.14}_{-0.08}$. We conclude that the CO low-J line ratios vary across environments in such a way that they can trace changes in the molecular gas conditions, with the main driver being changes in temperature.